2012
DOI: 10.1089/gtmb.2012.0235
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Associations and Epistatic Effects of theCCR5Promoter andCCR2-V64I Polymorphisms on Susceptibility to HIV-1 Infection in a Northern Han Chinese Population

Abstract: The outcome of human immunodeficiency virus (HIV)-1 infection and course to AIDS are variable among individuals. Both chemokine receptor 5 (CCR5) and CCR2 gene polymorphisms play essential roles in the susceptibility of HIV-1 infection. To investigate the main and epistatic effects of the CCR5 promoter and CCR2-V64I polymorphisms on HIV-1 infection in the Northern Han Chinese, subjects of 91 HIV-1-infected patients and 91 health controls were recruited. Single-nucleotide polymorphisms (SNPs) in the CCR5 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In this sense, the SNPs that had this associative character were as follows: T mutant allele of rs1800024 in Chinese population; 58 C mutant allele of rs1799988 in North and South Korean populations; 51 the A wild allele of rs1800023 in Indian population; 48 the A wild allele of rs1799987 in the U.S. population; 45 the A mutant allele of rs1800023 in Japanese population; 38 C wild allele of rs41469351 in Indian population; 63 the A wild allele of rs1799987 in Papua New Guinea, the United States, Senegal, Guinea, Sierra Leone, Ivory Coast, and Ghana populations; the A wild allele of rs1799987 in the U.S. population; 64 the GG genotype of rs1799987 in Cameroon population. 59 The SNP most often associated with susceptibility was rs1799987, present in four studies (12.5%), under the presence of the wild-type A allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the SNPs that had this associative character were as follows: T mutant allele of rs1800024 in Chinese population; 58 C mutant allele of rs1799988 in North and South Korean populations; 51 the A wild allele of rs1800023 in Indian population; 48 the A wild allele of rs1799987 in the U.S. population; 45 the A mutant allele of rs1800023 in Japanese population; 38 C wild allele of rs41469351 in Indian population; 63 the A wild allele of rs1799987 in Papua New Guinea, the United States, Senegal, Guinea, Sierra Leone, Ivory Coast, and Ghana populations; the A wild allele of rs1799987 in the U.S. population; 64 the GG genotype of rs1799987 in Cameroon population. 59 The SNP most often associated with susceptibility was rs1799987, present in four studies (12.5%), under the presence of the wild-type A allele.…”
Section: Discussionmentioning
confidence: 99%
“…However, the polymorphisms that had an associative character with HIV-1 protection were the SNPs: G mutant allele of rs2856758 in Chinese population; 58 G mutant allele of rs1799987 in Polish population; 53 G mutant allele of rs1799987 in Indian population. 54 The SNP most associated with protection was also rs1799987, in two of the three studies of resistance conferred to infection (75%), under presence of the G mutant allele.…”
Section: Discussionmentioning
confidence: 99%
“…These two variants (represented by the HHF*2 haplotype) have been seen to associate with lower viral loads in an African population but did not have a significant association with transmission [3], and a significant association with decreased transmission was observed in a Columbian cohort [35]. However, a study in a Chinese population found a significant association with increased transmission for the CCR5 rs1800024 variant and a non-significant but similarly oriented association for the CCR2 allele [36]. It is very likely that the genetic background in different ethnic groups is a strong modifier on the association of these variants with risk of transmission, and should be studied in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is located on chromosome 3 in proximity to the CCR5 gene. A mutation in the coding region of the CCR2 gene, V64I, has shown to be in strong linkage disequilibrium with the mutation −1835T in the promoter region of the CCR5 gene (Kostrikis et al ., ; Lu et al ., ).…”
Section: Introductionmentioning
confidence: 97%